Analisis Kualitas Layanan Toko Online terhadap Kepuasan Masyarakat - Samvara, Made Adhiguna; -, Hidayanti (Jurnal Ekonomi Bisnis Manajemen Prima, 2020)
Online stores are generally known as e-commerce or electronic commerce is an industry type where the sale and purchase of products / services is done through the internet media. As we all know, the development of online business in Indonesia continues to experience rapid increase and progress by using internet media. This study aims to determine the types of online store services that are most often complained of by people in Medan in the use of buying and selling transactions,  how does the influence of the quality of online shop services on the satisfaction of public transactions in the city of Medan,  service quality factors that have a dominant influence on the satisfaction of people in the Medan City transaction and what improvement efforts should be made by the online store company in improving the quality of service to achieve satisfaction of public transactions in the city of Medan. The hypothesis of this study is the quality of service significantly influences the satisfaction of the people of Medan. The results showed that the service most frequently complained by the people was that the goods purchased did not match what was received. The results also showed that the quality of services provided by the company affected the level of satisfaction of public transactions in the city of Medan with a coefficient of determination of 66.2% variable reliability was the most dominant determinant of service quality that could increase the satisfaction of public transactions in the city of Medan.